2012
DOI: 10.1093/cid/cis290
|View full text |Cite
|
Sign up to set email alerts
|

Does Lipid Emulsion Reduce Amphotericin B Nephrotoxicity? A Systematic Review and Meta-analysis

Abstract: This meta-analysis of 13 studies revealed that amphotericin B delivered as a locally prepared lipid emulsion or in liposomes reduced nephrotoxicity to a similar degree, by 18.4% (relative risk [RR], 0.40 [99% confidence interval, .25-.64]; n = 459) and 18.1% (RR, 0.48 [99% CI, .36-.64]); n = 1233), respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 9 publications
1
54
0
1
Order By: Relevance
“…Liposomal AmB has an improved renal safety profile compared to conventional AmB. 61 Two pathogenic mechanisms have been suggested to explain AKI with AmB use. 62 The antifungal effect of AmB is related to its ability to alter membrane permeability of fungal cells, which leads to cell death.…”
Section: Antifungal Agents Amphotericin Bmentioning
confidence: 99%
“…Liposomal AmB has an improved renal safety profile compared to conventional AmB. 61 Two pathogenic mechanisms have been suggested to explain AKI with AmB use. 62 The antifungal effect of AmB is related to its ability to alter membrane permeability of fungal cells, which leads to cell death.…”
Section: Antifungal Agents Amphotericin Bmentioning
confidence: 99%
“…Mistro and coworkers (9) systematically reviewed the literature on AmB-induced AKI and assessed whether drug delivery in a locally prepared lipid emulsion or in liposomes reduced nephrotoxicity (9). In their meta-analysis, the authors summarized nine clinical trials comparing AmB in 5% dextrose with AmB in lipid emulsion and found an overall incidence of nephrotoxicity in 30.6% versus 12.2% of cases, respectively.…”
mentioning
confidence: 99%
“…The high rate of nephrotoxicity has led to the development of AmB formulations in three different lipid bases: lipid complex, colloidal dispersion, and liposomal [21]. While lipid formulations of AmB were found to be less nephrotoxic than other formulations of the drug, these formulations do not completely eliminate nephrotoxicity.…”
Section: Discussionmentioning
confidence: 99%